Generative AI navigating the course to the Artificial general intelligence future - Musiol, Martin (John Wiley & Sons, 2024)
An engaging and essential discussion of generative artificial intelligence In Generative AI: Navigating the Course to the Artificial General Intelligence Future, celebrated author Martin Musiol--founder and CEO of generativeAI.net and GenAI Lead for Europe at Infosys--delivers an incisive and one-of-a-kind discussion of the current capabilities, future potential, and inner workings of generative artificial intelligence. In the book, you'll explore the short but eventful history of generative artificial intelligence, what it's achieved so far, and how it's likely to evolve in the future. You'll also get a peek at how emerging technologies are converging to create exciting new possibilities in the GenAI space. Musiol analyzes complex and foundational topics in generative AI, breaking them down into straightforward and easy-to-understand pieces. You'll also find: Bold predictions about the future emergence of Artificial General Intelligence via the merging of current AI models Fascinating explorations of the ethical implications of AI, its potential downsides, and the possible rewards Insightful commentary on Autonomous AI Agents and how AI assistants will become integral to daily life in professional and private contexts Perfect for anyone interested in the intersection of ethics, technology, business, and society--and for entrepreneurs looking to take advantage of this tech revolution--Generative AI offers an intuitive, comprehensive discussion of this fascinating new technology.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on February 07, 2024)
Keywords: Artificial intelligence; Intelligence artificielle; artificial intelligence; Informational works; Documents d'information